Artificial intelligence ethics in authoritarian Vietnam: governance, trust, and societal tensions - Huong T. Tran; Bac H. Dang; Mai T. T. Nguyen; Quynh T. T. Pham; Phuoc V. Nguyen (Policy Design and Practice, 2025)
This study investigates the ethical challenges of artificial intelligence (AI) deployment in Vietnam, driven by the need to understand how authoritarian governance and public trust shape technology’s societal impact in a rapidly modernizing state. The objective is to analyze the governance-trust interplay, identifying ethical dilemmas and their implications in Vietnam’s single-party context. Employing a qualitative approach, the research draws on policy documents, semi-structured interviews with policymakers, developers, and citizens, social media analysis, and case studies of facial recognition in Hanoi and AI in public health. Results reveal that Vietnam’s centralized governance enables swift AI adoption but falters in ethical flexibility and accountability, evident in privacy concerns and unclear responsibility for errors. Public trust varies, supported by state narratives in urban areas yet weakened by opacity and rural digital divides. The governance-trust dynamic shows transparency deficits undermining confidence, countered by societal resistance prompting modest policy adjustments. The study concludes that AI in Vietnam is a socio-political process with ethical stakes, offering a non-Western perspective to global debates and insights for aligning innovation with societal well-being.